Rehydration Compensation of Winter Wheat Is Mediated by Hormone Metabolism and De-Peroxidative Activities Under Field Conditions - Liu, Xuejing; Wang, Xiaodong; Liu, Pan; Bao, Xiaoyuan; Hou, Xiaoyang; Yang, Mingming; Zhen, Wenchao (Frontiers in Plant Science, 2022)
Water deficit and rehydration frequently occur during wheat cultivation. Previous investigations focused on the water deficit and many drought-responsive genes have been identified in winter wheat. However, the hormone-related metabolic responses and de-peroxidative activities associated with rehydration are largely unknown. In this study, leaves of two winter wheat cultivars, “Hengguan35” (HG, drought-tolerant cultivar) and “Shinong086” (SN, drought-sensitive cultivar), were used to investigate water deficit and the post-rehydration process. Rehydration significantly promoted wheat growth and postponed spike development. Quantifications of antioxidant enzymes, osmotic stress-related substances, and phytohormones revealed that rehydration alleviated the peroxidation and osmotic stress caused by water deficit in both cultivars. The wheat cultivar HG showed a better rehydration-compensation phenotype than SN. Phytohormones, including abscisic acid, gibberellin (GA), jasmonic acid (JA), and salicylic acid (SA), were detected using high-performance liquid chromatography and shown to be responsible for the rehydration process. A transcriptome analysis showed that differentially expressed genes related to rehydration were enriched in hormone metabolism- and de-peroxidative stress-related pathways. Suppression of genes associated with abscisic acid signaling transduction were much stronger in HG than in SN upon rehydration treatment. HG also kept a more balanced expression of genes involved in reactive oxygen species pathway than SN. In conclusion, we clarified the hormonal changes and transcriptional profiles of drought-resistant and -sensitive winter wheat cultivars in response to drought and rehydration, and we provided insights into the molecular processes involved in rehydration compensation.